The Jews of Iraq 3000 years of history and culture - Rejwan, Nissim 1924- (Routledge, 2019)
This book provides an account of the Jews of Iraq, their history, culture and society. It covers the Iraqi Jewish history in three parts: from the Assyrian Captivity to the Arab Conquest (731 bc-ad 641); the encounter with Islam (641-1850); and the last hundred years (1850-1951)
Keywords: Jews / Iraq / History; Iraq / Ethnic relations; Juifs / Irak / Histoire; Irak / Relations interethniques; HISTORY / General; Ethnic relations; Jews; Iraq; Juden; Electronic books; History